The Effect of Taxol on some Blood Parameters and Study of Histopathological Changes in the Kidneys of Laboratory Rats: Pengaruh Taxol terhadap beberapa Parameter Darah dan Studi Perubahan Histopatologi pada Ginjal Tikus Laboratorium - Hammood, Zahraa Y.; Rashid, Alaa R. (Indonesian Journal on Health Science and Medicine, 2025)
Taxol is a microtubule inhibitor drug widely used in treatment of many types of cancer. In the present study Taxol at different doses if the rats were randomly divided into three groups, each group containing 12 laboratory rats, as follows: The control group consisted of 12 rats injected with 0.5 ml of distilled water. The low dose group consisted of 12 rats injected with 2 mg/kg of Taxol intraperitoneally. The high dose group consisted of 12 rats injected with 4 mg/kg of Taxol intraperitoneally. The results of histological examination of tissue sections showed pathological histological changes in the kidneys of laboratory rats. The results of the current study showed a significant decrease below the probability level of P≤0.05 in blood parameters including white blood cell count and percentage of lymphocytes, neutrophils, eosinophils and basophils in laboratory rats treated with (TAXOL) at two doses (2.4 mg/kg). The results of the study showed a significant decrease in the number of red blood cells below the probability level of P≤0.05 at both high and low doses, noting that the effect of the high dose was greater than the low dose. The results of histological sections of the kidneys of laboratory rats treated with Taxol showed blood congestion in the blood vessels with degenerations in the proximal and distal endothelial cells and atrophy of the renal glomeruli Highlights: Groups: Control, 2 mg/kg Taxol, 4 mg/kg Taxol (n=12/group). Blood: Taxol reduced WBC, RBC, lymphocytes, neutrophils significantly (P≤0.05). Kidney: Congestion, cell degeneration, glomerular atrophy observed in treated rats. Keywords: Taxol, Chemotherapy, nephrotoxicity, Hematological